Amikasin: Profil Penggunaan pada Pasien Dewasa Rawat Inap di RSUP Dr.Sardjito Yogyakarta berdasarkan Fungsi Ginjal - Utami, Esti Dyah; Puspitasari, Ika; Asdie, Rizka Humardewayanti; Lukitaningsih, Endang; Dahesihdewi, Andaru (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Amikacin is used for serious infection treatment, with a nephrotoxicity incidence of 3-13%. More than 90% of amikacin is excreted through the renal in unchanged form, thus accumulation may occur in renal dysfunction. This research is aimed to determine the amikacin usage profiles based on the patient’s renal function and evaluate the association between a renal function with hospital discharge conditions and length of stay (LOS). This research was conducted by collecting the medical record data of adult inpatients at Dr. Sardjito Hospital treated with amikacin in 2020. A Chi-Square test was used to determine the proportion differences between 2 groups of patients with different renal functions, and the relationship of renal function with discharge condition and LOS. The majority of 78 subjects had normal renal function, with a diagnosis of mixed infection. Amikacin was used as definitive therapy, as an antibiotic combination, with a median dosage of 14.3mg/kgBW/day, 12 hours interval, and 5 days duration. Results showed that the CrCl, infection type, comorbid, amikacin intervals and duration had significantly different proportions (p<0.05) between patients with normal renal function and those with renal dysfunction. Renal function was positively associated with the patient’s discharge condition, but not with LOS.